Irregular Wave Groups Simulation Based on Semi-Mixed Eulerian-Lagrangian Boundary Element Method - XUE Wen, GAO Zhiliang (Shanghai Jiaotong Daxue xuebao)
In order to effectively simulate irregular wave groups that better represent the characteristics of real waves, a numerical wave tank based on a semi-mixed Eulerian-Lagrangian algorithm combined with boundary element method was developed in conjunction with a theoretical generation method for irregular wave groups. First, the impact of model parameters on the numerical solution was analyzed. The results showed that the accuracy of wave simulation improved with an increase in damping layer length or a decrease in the time step. Additionly, selecting appropriate deviation distance, distribution range, and the number of source points can balance computation accuracy and stability. Then, unidirectional irregular wave groups were simulated based on the verified model parameters. The numerical results were compared with the physical test data and theoretical values to validate the performance of the numerical tank in simulating irregular wave groups. The findings indicated that the developed numerical wave tank can effectively simulate the generation and propagation of irregular wave groups.